A small molecule targeting glutathione activates Nrf2 and inhibits cancer cell growth through promoting Keap-1 S-glutathionylation and inducing apoptosis. Issue 2 (3rd January 2018) - Wang, LiHong; Qu, GuoJing; Gao, YuanDi; Su, Le; Ye, Qing; Jiang, Fan; Zhao, BaoXiang; Miao, JunYing
Abstract : The level of glutathione (GSH) is increased in many cancer cells. Abstract : The level of glutathione (GSH) is increased in many cancer cells. Consuming intracellular GSH by chemical small molecules that specifically target GSH is a new strategy to treat cancer. Recently, we synthesized and proved that a new compound 2-(7-(diethylamino)-2-oxo-2 H -chromen-3-yl)cyclohexa-2, 5-diene-1, 4-dione (PBQC) could target to and consume intracellular GSH specifically, but, it is not clear if PBQC can affect cancer cell growth and the activity of the nuclear factor-erythroid 2-related factor 2 (Nrf2) which is a key factor involved in regulation of cancer cell growth. In this study, we addressed these questions. We found that PBQC suppressed cancer cell growth through increasing the activity of Nrf2, while it did not inhibit normal vascular endothelial cell growth. Furthermore, we demonstrated that PBQC can cause Keap-1 protein S -glutathionylation and promote Nrf2 nuclear translocation as well as the expression of pro-apoptosis genes. As a result, the cancer cells underwent apoptosis. Here, we provide a new Nrf2 activator, PBQC that can promote the expressions of pro-apoptosis genes downstream Nrf2. The data suggest that PBQC is a potential lead-compound for development of new anti-cancer drugs.